Probability, Stochastic Processes and Optimization (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint encompasses all the articles that have been accepted and published in the Special Issue entitled "Probability, Stochastic Processes and Optimization". In applied research, Probability Theory is usually regarded as a distant, often-neglected relative of Statistics. This Special Issue attempted to rectify this misconception by publishing papers presenting novel applications and original models from the natural, computer, or social sciences, based on Probability and Stochastic Processes.